Optical and structural characterization of oleic acid-stabilized CdTe nanocrystals for solution thin film processing - Gutiérrez Lazos, Claudio Davet; Ortega López, Mauricio; Pérez Guzmán, Manuel A.; Espinoza Rivas, A. Mauricio; Solís Pomar, Francisco; Ortega Amaya, Rebeca; Silva Vidaurri, Luis Gerardo; Castro Peña, Virginia Carolina; Pérez Tijerina, Eduardo (Beilstein-Institut zur Förderung der Chemischen Wissenschaften, 2014)
This work presents results of the optical and structural characterization of oleic acid-stabilized cadmium telluride nanocrystals (CdTe-NC) synthesized by an organometallic route. After being cleaned, the CdTe-NC were dispersed in toluene to obtain an inklike dispersion, which was drop-cast on glass substrate to deposit a thin film. The CdTe-NC colloidal dispersion as well as the CdTe drop-cast thin films were characterized with regard to the optical and structural properties. TEM analysis indicates that the CdTeNC have a nearly spherical shape (3.5 nm as mean size). Electron diffraction and XRD diffraction analyses indicated the bulk-CdTe face-centered cubic structure for CdTe-NC. An additional diffraction line corresponding to the octahedral Cd3P2 was also detected as a secondary phase, which probably originates by reacting free cadmium ions with trioctylphosphine (the tellurium reducing agent). The Raman spectrum exhibits two broad bands centered at 141.6 and 162.3 cm−1, which could be associated to the TO and LO modes of cubic CdTe nanocrystals, respectively. Additional peaks located in the 222 to 324 cm−1 range, agree fairly well with the wavenumbers reported for TO modes of octahedral Cd3P2.